Comparison of the Vaginal Microbiomes of Premenopausal and Postmenopausal Women - Gliniewicz, Karol; Schneider, G. Maria; Ridenhour, Benjamin J.; Williams, Christopher J.; Song, Yuli; Farage, Miranda A.; Miller, Kenneth; Forney, Larry J. (Frontiers in Microbiology, 2019)
For decades hormone therapy (HT) has been prescribed to treat the symptoms of menopause, such as vaginal dryness, itching and burning. Here we sought to compare the vaginal microbiomes of post-menopausal women who received low dose estrogen therapy to those of premenopausal and postmenopausal women, and to do so in conjunction with assessing the alleviation of symptoms associated with vaginal atrophy. In this study vaginal swab samples were obtained from 45 women who were classified as either premenopausal, postmenopausal, or post-menopausal and undergoing HT. The vaginal microbiomes of these women were characterized by 16S rRNA gene sequencing and bacterial abundances were quantified by qPCR. We found that the vaginal communities from our cohort could be divided into six groups (A-F) based on differences in the composition and relative abundances of bacterial taxa. Communities in group A were dominated by Lactobacillus crispatus, and those of group B were dominated by Gardnerella vaginalis. Communities in group C had high proportions of L. iners, while those in group D were more even and included several co-dominant taxa. Communities in groups E and F were dominated by Bifidobacterium and L. gasseri, respectively. The vaginal communities of most post-menopausal women receiving HT (10/15) were dominated by species of lactobacilli and belonged to groups A, C, and F (p < 0.001). This sharply contrasts with vaginal communities of post-menopausal women without HT, most of which (10/15) were in group D, depleted of lactobacilli, and had about 10-fold fewer total bacteria (p < 0.05). The vaginal communities of women in each study group differed in terms of the dominant bacterial species composition and relative abundance. Those of postmenopausal women receiving HT significantly differed from those of postmenopausal women without HT and were most often dominated by species of Lactobacillus. Noteworthy, HT greatly improved vaginal atrophy scores, decreased vaginal pH, and significantly increased bacterial numbers in comparison to postmenopausal women not receiving HT.